Acid mine drainage treatment by coagulation process using a synthesized sulphate-based coal fly ash coagulant - Apua, Momboyo Clotilde (My University, 2021)
The study focused on the synthesis of a composite coagulant containing polymeric sulphates of Fe, Al, Si, Mg, and Ca from coal fly ash (CFA).
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2020